2015
DOI: 10.1097/qco.0000000000000194
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis

Abstract: Leishmaniasis remains a neglected tropical disease, with a need for additional clinical trials with better design and reported endpoints to lead evidence-based treatment recommendations--especially in cutaneous leishmaniasis and leishmaniasis in the immunocompromised host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Subsequently, several major clinical guidelines have been published, but they were not targeted toward clinical management in North America [13]. In the USA, there is a dichotomous dilemma with the diagnosis and care of patients with leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several major clinical guidelines have been published, but they were not targeted toward clinical management in North America [13]. In the USA, there is a dichotomous dilemma with the diagnosis and care of patients with leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…For patients similar to ours a combination treatment could be an alternative, although there is currently not enough international data to judge the value of this approach [11]. However, studies in India have demonstrated excellent efficacy of short combination therapy and according to expert opinion, combination therapy will probably become the standard of VL treatment in the future which will allow to shorten treatment regimens, thus reducing treatment related toxicity, as well as preventing emergence of drug resistance [12].…”
Section: Discussionmentioning
confidence: 99%
“…[6] Coinfection leads to increased treatment failure, relapse, drug toxicity, and mortality. [7] In HIV-infected patients, cutaneous dissemination is common in visceral leishmaniasis. [2] Furthermore, atypical lesions and relapses of the disease are common in these patients.…”
Section: Discussionmentioning
confidence: 99%